ANALISIS TUJUAN PEMBANGUNAN KESATUAN PENGELOLAAN HUTAN (KPH) DI PAPUA - Irma Yeny; Haryatno Dwiprabowo (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
In the context of planning, Development goals of Forest Management Unit (FMU) should be defined as target indicators, strategies to achieve the goals and development plans and to manage activities. FMU in Papua Province is in the stages of institutional formation and its policy supporting tools like other provinces in Indonesia. This study aimed to identify development goals of FMU based on the perception of stakeholders, so it could be used as measureable performance indicators. The research was conducted on the model FMU of Papua and West Papua provinces. Data were collected through interviews using structured questionnaires, and then analyzed by Analysis Hierarchy Process (AHP). The results showed that the goals of forest function maintaining and environment carrying capacity were the important factors of FMU Development in Papua. These were in line with development objectives of FMU development written on document of FMU design and stakeholder interests that should ensure the sustainability of ecological functions. There were six measurable outcome indicators to obtain the development of FMU in Papua.